Reporting Politics: A Political Journalism Study from the Perspectives of Journalists in Malang Raya - Alfira, Nisa; Maudy Apsari, Kendita Agustin; Rachmad Gustomy,; Apriliyanti, Sabrina Afia (Mediakita, 2023)
PPolitical journalism as a field of study under the banner of journalism study, needs to be explored deeper in the context of Indonesia. Indonesia is one of the biggest democratic countries in the world. The country has implemented the system of direct elections in every five years to elect regional leaders as well as president and vice president. This paper aims to shed light on the practice of political journalism in Malang Raya. Malang Raya is a region in East Java Province which is comprised of Kota Malang, Kabupaten Malang and Kota Batu. The writers conducted semi-structured interviews with 6 reporters. The findings of this research are: (i) journalist and contributors do not obtain a complete freedom in the process of gathering the news and writing the news; (ii) journalist and contributors have obeyed the Indonesian ethics of journalistic, and (iii) to some extent, there are some factors influencing political reporting, i.e.: the interests of media firms, local culture, and geographical locations. Furthermore, politics is an interesting and challenging issue to report. Journalists can face some challenges and problems in reporting politics, as it also happened to our informants. In general, media firms have capacity to interpret the politicians conduct, and influence voters behaviour. In return, politicians are also in need of media, in terms of disseminating their ideas and obtaining some information about the communities.